Continuous wave electron paramagnetic resonance of nitroxide biradicals in fluid solution. (25th May 2018) - Eaton, Sandra S.; Woodcock, Lukas B.; Eaton, Gareth R.
Abstract: Nitroxide biradicals have been prepared with electron‐electron spin‐spin exchange interaction, J, ranging from weak to very strong. EPR spectra of these biradicals in fluid solution depend on the ratio of J to the nitrogen hyperfine coupling, A N, and the rates of interconversion between conformations with different values of J . For relatively rigid biradicals EPR spectra can be simulated as the superposition of AB splitting patterns arising from different combinations of nitrogen nuclear spin states. For more flexible biradicals spectra can be simulated with a Liouville representation of the dynamics that interconvert conformations with different values of J on the EPR timescale. Analysis of spectra, factors that impact J, and examples of applications to chemical and biophysical problems are discussed.